2021
DOI: 10.1002/jsfa.11428
|View full text |Cite
|
Sign up to set email alerts
|

Wheat grain phenolics: a review on composition, bioactivity, and influencing factors

Abstract: Wheat (Triticum aestivum L.) is a widely cultivated crop and one of the most commonly consumed food grains in the world. It possesses several nutritional elements. Increasing attention to wheat grain phenolics bioactivity is due to the increasing demand for foods with natural antioxidants. To provide a comprehensive understanding of phenolics in wheat grain, this review first summarizes the phenolics' form and distribution and the phenolic components identified in wheat grain. In particular, the biosynthesis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 171 publications
(212 reference statements)
0
30
0
Order By: Relevance
“…Widely targeted metabolome enables the identification of more phenolic compounds, but the detected metabolites are relatively quantitative. It is widely accepted that the antioxidant activities of phenolic compounds were significantly different ( 10 , 43 ). Exploring the substances with high bioactive components in HP512 and verifying their activity in vivo need to be done.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Widely targeted metabolome enables the identification of more phenolic compounds, but the detected metabolites are relatively quantitative. It is widely accepted that the antioxidant activities of phenolic compounds were significantly different ( 10 , 43 ). Exploring the substances with high bioactive components in HP512 and verifying their activity in vivo need to be done.…”
Section: Discussionmentioning
confidence: 99%
“…Orientin and isoorientin were significantly and highly overexpressed in immature grains (30 DAA), indicating that HPm512 can be used for the production of food rich in bioactive substances even in immature grains. It is widely known that planting environment has a significant effect on grain phenolics content ( 10 ). We have to mention that although total phenolics content of HPm512 varied in different planting conditions, its relative abundance was significantly higher than that of control ZM22, which confirmed that HPm512 has potential health benefits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations